PSYCHOLOGICAL CHILD hyperactive DEVELOPMENT APPLICATIONS INFORMATION USING MICROSOFT VISUAL BASIC 6.0 - Sulistrianingsih Sulistrianingsih; Ristyawati Ristyawati, SKom., MMSI (Jurnal Sistem Informasi, 2007)
This writing describes the Application Development Psychology InformationHyperactive Child as a source of information which at the present time a child ishyperactive children tend to be equated with active. This condition is very difficult toexplain because many normal children who constantly moving. But the hyperactivechild is never quiet and no one locked their attention, whereas the tendency ofchildren to be active have a smart kid. The purpose of the presentation is that we cangain a broader information about the special treatment for hyperactive children.While this kind of knowledge about the psychology of child development informationis still very minimal hyperactive. To the writer wants to display them in computerizedform by using Microsoft Visual Basic 6.0. by presenting it in the form ofcomputerized authors hope to provide ease of information to parents in particularknowledge, which has a hyperactive child.